2019
DOI: 10.1029/2018jc014488
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution and Biogeochemical Cycling of Dimethylated Sulfur Compounds and Methane in the East China Sea During Spring

Abstract: The spatial distributions of dimethylsulfide (DMS), dimethylsulfoniopropionate (DMSP), dimethylsulfoxide (DMSO), and methane (CH4) were studied in the East China Sea during May 2017, and the possible controlling factors and biogeochemical cycling processes are discussed. The mean surface concentrations of DMS and CH4 were 10.66 and 9.93 nmol/L in the coastal area and 7.60 and 6.88 nmol/L in the open ocean, respectively. Horizontal and vertical profiles of the dimethylated sulfur compounds and CH4 were largely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 85 publications
(131 reference statements)
2
8
0
Order By: Relevance
“…The DMS concentrations were generally between 1.1 and 3.5 nmol L −1 , except for two small peaks of up to 9.5 nmol L −1 in areas of phytoplankton blooms near the eastern region of Hainan and the estuarine region of the Pearl River (Figure ). Our results were in agreement with those of many previous studies (Zhai et al, ; Zhang et al, ), in which high DMS levels commonly occurred in the estuaries and were related to the high phytoplankton biomass. Overall, the DMS concentrations were high in the estuarine and coastal regions and low in the central large‐scale basin.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The DMS concentrations were generally between 1.1 and 3.5 nmol L −1 , except for two small peaks of up to 9.5 nmol L −1 in areas of phytoplankton blooms near the eastern region of Hainan and the estuarine region of the Pearl River (Figure ). Our results were in agreement with those of many previous studies (Zhai et al, ; Zhang et al, ), in which high DMS levels commonly occurred in the estuaries and were related to the high phytoplankton biomass. Overall, the DMS concentrations were high in the estuarine and coastal regions and low in the central large‐scale basin.…”
Section: Resultssupporting
confidence: 94%
“…Many studies have demonstrated that the production and consumption of DMS are significantly affected by the complex web of ecological, physical, and biogeochemical processes (Asher et al, ; Kiene et al, ; Simó et al, ; Zhai et al, ). Oceanic DMS is mainly derived from the algal and bacterial metabolite of dimethylsulfoniopropionate (DMSP) (Keller, ; Todd et al, ), which is produced by phytoplankton.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vertical distribution of VOSCs in lakes differed significantly from that in the ocean, where the concentration of VOSCs decreased with depth [38]. Concentrations of DMS in the surface water of Yangcheng Lake were higher than those in the open sea (0.12 µg/L) and comparable to those in the offshore area (0.62 µg/L) [39][40][41].…”
Section: Compared With Other Freshwater Lakesmentioning
confidence: 81%
“…The predicted high MOx rates in near-shore environments suggest that this process could serve as an important biological sink to reduce the global diffusive methane emissions from shallow waters. Furthermore, we also predicted depth profiles of MOx rates in the ECS using this model based on the previous measurements of methane concentrations and other parameters in the ECS 43 (Supplementary Table 3). The predicted depth-integrated MOx rates (22.08 ± 7.92 µmol m −2 d −1 ) were similar to the measured values, verifying the validity of our model.…”
Section: Predicted Global Mox Rates In Marine Watersmentioning
confidence: 99%